2016
DOI: 10.1177/0148607116629670
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Perioperative Probiotics and Synbiotics on Postoperative Infections After Gastrointestinal Surgery: A Systematic Review With Meta‐Analysis

Abstract: Probiotics and synbiotics may prevent postoperative infections in patients undergoing gastrointestinal surgery. However, the results need to be interpreted with caution due to the risk of bias in the included studies and the potential publication bias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 43 publications
0
38
0
Order By: Relevance
“…Another meta-analysis that included 28 RCTs (n = 2511) involving adult patients undergoing gastrointestinal surgery came to similar conclusions (Yang et al, 2017). The durations of hospital stay and antibiotic therapy were shorter in the probiotics/symbiotic group vs controls (Yang et al, 2017).…”
Section: Probiotics For Cgiscmentioning
confidence: 84%
See 3 more Smart Citations
“…Another meta-analysis that included 28 RCTs (n = 2511) involving adult patients undergoing gastrointestinal surgery came to similar conclusions (Yang et al, 2017). The durations of hospital stay and antibiotic therapy were shorter in the probiotics/symbiotic group vs controls (Yang et al, 2017).…”
Section: Probiotics For Cgiscmentioning
confidence: 84%
“…Another meta-analysis that included 28 RCTs (n = 2511) involving adult patients undergoing gastrointestinal surgery came to similar conclusions (Yang et al, 2017). The durations of hospital stay and antibiotic therapy were shorter in the probiotics/symbiotic group vs controls (Yang et al, 2017). The need for caution in interpreting the results was emphasized considering the high risk of bias in included studies (Lytvyn et al, 2016;Yang et al, 2017).…”
Section: Probiotics For Cgiscmentioning
confidence: 92%
See 2 more Smart Citations
“…A recently performed systematic review with metanalysis of 28 randomized controlled trials involving 2511 patients revealed that the use of these substances has the potential to reduce the incidence of wound infections. (27) Specifically, studies using combination of two or more probiotic strains were associated with significant outcomes. This is of no surprise, as one bacterial strain is unlikely to promote reinstatement of the complex community structure and function of the health-promoting intestinal microbiome.…”
Section: Intestinal Microbiome and Surgical Site Infectionsmentioning
confidence: 99%